Prem Rawat and counterculture: Glastonbury and new spiritualities - Geaves, Ron (Bloomsbury Academic, 2020)
Introduction -- Theorizing new age and contemporary spiritualities -- Easternization : Indian gurus and the west -- Prem Rawat and contextualizing Indian religions in the west -- Festivals and music : counterculture's religiosity? -- The significance of Glastonbury -- Prem Rawat at Glastonbury : occulture and easternization? -- The aftermath of Glastonbury Fayre : Prem Rawat and counterculture --Counterculture, occulture and easternization revisited -- Postscript.